A Glance At Internal And External Qualities Of Kuttanad, White Pekin And Commercial Duck Eggs - Harikrishnan, S.; Ponnuvel , P. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
A study was carried out to determine the egg qualities of farm fresh Kuttanad and White Pekin duck eggs of the institute and eggs collected from various shops in and around Thrissur district, Kerala. A total of 42 eggs were subjected to evaluate the internal and external quality parameters. The results revealed that there is no significant difference among mean egg weight, shape index and specific gravity. Kuttanad and White Pekin farm fresh eggs showed significantly (P<0.05) superior quality in shell thickness, shell percentage and yolk index. Albumen index and Haugh unit score of Kuttanad duck eggs were significantly (P<0.05) superior to White Pekin eggs and market eggs showed the least. Mean shell weight value of White Pekin eggs were significantly higher than market eggs while there was no significant difference between Kuttanad and White Pekin eggs. Yolk score of market egg (8.67 ±0.31) was significantly higher than the farm fresh eggs (6.67±0.24 and 5.33±0.24).